Effect of germination environment on the biochemical compounds and anti-inflammatory properties of soybean cultivars - Eum, Hyang Lan; Park, Yeri; Yi, Tae Gyu; Lee, Jae Wook; Ha, Keon-Soo; Choi, Ik-Young; Park, Nam Il (PUBLIC LIBRARY SCIENCE, 2020)
In this study, we investigated changes in the isoflavone content, total phenolic content (TPC), total flavonoid content (TFC), antioxidant activities (DPPH, ABTS), and anti-inflammatory activities of small-seeded and large-seeded soybean cultivars during germination (light/dark conditions). Total isoflavone content was higher at the seed stage in large-seeded soybeans, while it increased after 7 days of germination in small-seeded soybeans, particularly in response to light conditions, under which they had high TPC, TFC, and anti-oxidant activities. In large-seeded soybeans, the germination environment did not significantly affect TFC or DPPH inhibition, whereas TPC and ABTS inhibition were high under dark germination conditions. Extracts of sprouts exhibited superior anti-inflammatory activities. Nitric oxide production was slightly lower in small-seeded and large-seeded soybeans germinated under light and dark conditions, respectively. Our findings indicate that germinated soybeans improved nutritionally, and that enhancement of bioactivity under different germination environments could contribute to the selection of appropriate soybean cultivars.
Keywords: GLYCINE-MAX L.; ISOFLAVONE